THE CHANGE OF CONTRAST IS INVESTIGATION OF 75 STEEL SAMPLES LASER MARKED WITH DIFFERENT MODES (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The quality of the marked surfaces changes the optical characteristics. The aim of the study is to optimize the contrast in laser marking of Steel 75. The influence of the step in the raster marking and the influence of the repetition frequency of the pulses on the reflection coefficient were analysed. The experimental investigations of the reflectance were carried out using a spectrophotometer. For the marked samples, it was found that when directing electromagnetic radiation with a wavelength in the studied range, there are areas with absorption and reflection of light. The reflectance is plotted as a function of marking step and laser frequency for the marked Steel 75 samples.